2012
DOI: 10.1158/1078-0432.ccr-11-2414
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical and Pharmacokinetic Evaluation of the Vascular-Disrupting Agent OXi4503 in Patients with Advanced Solid Tumors

Abstract: Purpose: Preclinical studies show that OXi4503 (combretastatin A1 diphosphate, CA1P) is more potent than other clinically evaluated vascular-disrupting agents.Experimental Design: Escalating doses of OXi4503 were given intravenously over 10 minutes on days 1, 8, and 15 every 28 days to patients with advanced solid tumors.Results: Doses were escalated in single-patient cohorts from 0.06 to 1.92 mg/m 2 , then expanded cohorts to 15.4 mg/m 2 in 43 patients. Common adverse drug reactions were hypertension, tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Taken together, these findings show that cardiac toxicity is not likely to be dose-limiting for STA-9584. This represents an important discriminating feature of the compound, because both hypertension (as a common adverse drug reaction) and atrial fibrillation (as a dose-limiting toxicity) have recently been reported in a phase I evaluation of Oxi4503 (Patterson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings show that cardiac toxicity is not likely to be dose-limiting for STA-9584. This represents an important discriminating feature of the compound, because both hypertension (as a common adverse drug reaction) and atrial fibrillation (as a dose-limiting toxicity) have recently been reported in a phase I evaluation of Oxi4503 (Patterson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A major difference between these two pathways is new vessels sprouting from existing vessels (angiogenesis) vs the influx of cells from other parts of the body or bone marrow, which can build or rebuild vessels (vasculogenesis). 115 Various vascular disrupting agents are also in clinical development, 116 and pre-clinical studies have suggested that these agents have potential to be combined with radiation, but apart from anecdotal observations in early stage trials, it is unclear if these will prove to be any more beneficial than antiangiogenic agents.…”
Section: Radiation-induced Damage To Vasculaturementioning
confidence: 99%
“…Current clinical data suggest that CA-1P is now the most potent clinically evaluated VTA (Patterson et al, 2012). Intriguingly, the vast majority of synthetic combretastatins are analogous to CA-4 despite emerging data demonstrating the superior therapeutic efficacy of CA-1 (Hua et al, 2003;Patterson et al, 2012). Similarly, combretastatin signaling pathways are primarily investigated using CA-4 and associated analogs.…”
Section: Future Directionsmentioning
confidence: 99%
“…The combretastatin A-1 diphosphate (CA-1P) and combretastatin A-4 phosphate (CA-4P) prodrugs were converted into their active counterparts over 7 times faster in tumor and liver preparations than in blood (Kirwan et al, 2004). The prodrugs soon became the preferred structures to progress to clinical trials (Young and Chaplin, 2004;Chaplin et al, 2006;Patterson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%